VITAMIN D TESTING IN ADULT PATIENTS: AN AUDIT IN HOSPITAL TELUK INTAN - Sun, Choon Peng; Saleh, Nursyahirah; Shari, Syazana Jan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Vitamin D deficiency is a prevalent condition associated with various health issues, including osteoporosis, fractures, metabolic disorders, and electrolyte imbalances like hypocalcemia. Despite its clinical importance, Vitamin D testing in Hospital Teluk Intan (HTI) is limited, requiring samples to be outsourced to Hospital Raja Permaisuri Bainun, with a turnaround time of approximately one week. This audit aims to assess the number of tests conducted, Vitamin D level distribution, and clinical indications for testing. METHODOLOGY This retrospective audit reviewed Vitamin D tests performed from January to December 2024. Adult patients (≥18 years) with completed test records were included, while pediatric patients and incomplete records were excluded. Data were collected from laboratory reports and clinical records. RESULT A total of 28 adult tests were conducted, with 24 females and 4 males. Among these, 75% were deficient (<50 ng/mL), 10.7% insufficient (50–74 ng/mL), and 14.3% sufficient (>75 ng/mL). The main clinical indications for testing were osteoporosis, rheumatoid arthritis, and thalassemia. Rheumatology had the highest test requests, followed by orthopedics and general medicine. CONCLUSION The audit highlights a low number of Vitamin D tests, with a high deficiency rate among patients. Limited test availability and delayed results may contribute to underdiagnosis. Raising awareness among healthcare providers, expanding test access, and integrating Vitamin D screening into routine care for high-risk patients could improve outcomes.